The development of Ottoman governments’ policies towards Greek associations, 1861-1912 - Karabıçak, Yusuf Ziya. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
This thesis aims to investigate the policies developed by Ottoman bureaucrats in their relations to Greek associations in the years between 1861 and 1912. These policies were constructed through the various documents the Ottoman bureaucrats produced while they were dealing with Greek associations. This study analyses these Ottoman correspondences focusing on the issues of Ottoman identity and the incorporation of Greek-speaking populations into the Ottoman political system. The focus of the thesis is on educational and philanthropic associations and their relations to the Ottoman bureaucrats. In this thesis Ottoman documents are presented in a way to link them with general developments among the Greek-speaking populations of the Empire and the perception of the Ottoman bureaucracy concerning an Ottoman identity. By focusing on the Ottoman bureaucrats’ perceptions and plans in these two fields, this thesis plans to contribute to the challenging of the standard historiography concerning Greek associations which deals with the issue in seclusion without paying attention to Ottoman governments’ plans and desires. The main body of sources used for this thesis consists of correspondences prepared by various Ottoman ministries and state departments in their relations to the Greek associations. Also, some legal texts prepared by Ottoman lawyers who lived in the years this thesis is concerned with and compilations of legal codes like Düstur and Mecelle-i Umur-ı Belediye were consulted.
Keywords: Greeks -- Turkey -- History.; Greeks -- Turkey -- Politics and government.